122k views
4 votes
Can someone explain how to do this please?

Can someone explain how to do this please?-example-1
User Sonie
by
5.4k points

1 Answer

4 votes


\bf \begin{cases} \boxed{y}=-2x\\\\ -x-y=4 \end{cases} \\\\[-0.35em] ~\dotfill\\\\ \stackrel{\textit{since we know what \boxed{y} is, let's substitute it in the 2nd equation}}{-x-\left( \boxed{-2x} \right)=4\implies -x+2x=4\implies x=4} \\\\[-0.35em] ~\dotfill\\\\ y=-2x\implies y=-2(4)\implies y=-8 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill (4,-8)~\hfill

User Ping
by
4.9k points